Biomonitoring agent for heavy metals run off from acid sulfate soil of aquaculture industries in Selangor, Malaysia - Othman, Rashidi; Mohd Hatta, Farah Ayuni; Shafiai, Shahima (2014)
The disturbance of acid sulfate soils due to poor wastewater management of aquaculture activities caused a major environmental issue such as metal pollution in coastal regions of many countries over the world. Peninsular Malaysia also challenged the same problem where it lost 18700 ha of coastal lowlands from 1980 to1990.This activity caused the oxidation of pyrite which produces high concentrations of ferrous ions, and sulfuric acid, in turn attacks clay minerals and produces high concentrations of monomeric aluminum (Al) and other acidsoluble metals. Subsequent leaching of these toxic products into adjacent water bodies is rapidly increasing the stress on ecosystems. Therefore, the research was aimed to monitor heavy metal runoff from acid sulfate soil at shrimp aquaculture areas through phytotechnology approach. The study was conducted at fourteen different sites in Selangor which contains large amount of acid sulfate soil. The result showed that Pistiastratiotes was substantially the best phytoindicator for Al, iron (Fe) and manganese (Mn) toxicity followed by Lemna.minor, Nymphaeastellata, and Urticulataaurea. On the other hand,N.stellatawas observed to be best phytoindicatorfor nickel (Ni), whereas for arsenic (As) was Ludwigiapalustris. Among these six species, the most potential biomonitoring agent to indicate acid-soluble metals are P.stratiotesand N.stellataas they are presence in low D.O level, high pH, high concentration of ammonium and tolerance to Al, Fe, Mn, and Ni.